Atomistic Insight into the Effects of Collision Angle on the Characteristics of Cu-Ta Joining by Explosive Welding - Van-Thuc Nguyen; Nguyen Quang Hien; Pham Minh Duc; Tran Duy Nam; Van Huong Hoang; Van Thanh Tien Nguyen (Metals)
This study aims to examine how the collision angle affects the Cu-Ta weld generated by the explosive welding method using molecular dynamics modeling. When two blocks collide, the metallic substrates melt rapidly. Subsequently, when heat energy dissipates to the surrounding areas, the weld interface begins rapidly cooling. Eventually, the weld joint’s surface shape and temperature stabilize. A meta-solid solution state between Cu and Ta could develop under extreme collision conditions of explosive welding through a dynamic diffusion mechanism. Furthermore, the plastic deformation process of the face-centered cubic (FCC) matrix after the explosive collision causes twin boundary scattering in the Cu substrate. The stress evolution experiences three stages: quick increasing, spreading out, and stabling. The stress mainly concentrates on the weld joint. Due to its dynamic recrystallization mechanism, the Cu substrate has a lower residual stress level than the Ta substrate. The atomic strain of the Cu-Ta weld joint improves dramatically as the impact angle increases. The high-strain zone extends toward the lower Ta block between 5° and 15°. Furthermore, the atomic strain and amorphous structure rates increase when the impact angles increase from 5° to 15°. After further improvement up to 20°, they then suffer a decrease. The Cu-Ta weld achieves a tensile strength ranging from 6.37 to 8.94 GPa. The Cu/Cu-Ta/Cu welding joint’s interface is coherent, transforming from an amorphous to a body-centered cubic (BCC) structure. Because of the dynamic diffusion mechanism at the interface, which creates an almost identical atomic rate between Cu and Ta atoms, combined with the dynamic recrystallization phenomenon, explosive welding provides the advantage of combining two low-solubility solid-solution metals.